2014
DOI: 10.1186/1478-4491-12-22
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of e-health innovations in ‘post-conflict’ settings: a qualitative study on the personal experiences of health workers

Abstract: BackgroundTechnological innovations have the potential to strengthen human resources for health and improve access and quality of care in challenging ‘post-conflict’ contexts. However, analyses on the adoption of technology for health (that is, ‘e-health’) and whether and how e-health can strengthen a health workforce in these settings have been limited so far. This study explores the personal experiences of health workers using e-health innovations in selected post-conflict situations.MethodsThis study had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 36 publications
4
35
3
1
Order By: Relevance
“…For example, the Diffusion of Innovation model (Woodward 2014) emphasises the importance of the socio-cultural context in which technology is used, such as social networks and cultural values, to understand the perceptions and experiences of those who use the technology. Likewise does the Health IT Usability Evaluation model (Brown 2013) offer nine concepts, including the flexibility of the technology to be used for more than one task, that shape users’ experiences and perceptions of the technology.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Diffusion of Innovation model (Woodward 2014) emphasises the importance of the socio-cultural context in which technology is used, such as social networks and cultural values, to understand the perceptions and experiences of those who use the technology. Likewise does the Health IT Usability Evaluation model (Brown 2013) offer nine concepts, including the flexibility of the technology to be used for more than one task, that shape users’ experiences and perceptions of the technology.…”
Section: Methodsmentioning
confidence: 99%
“…Information and communication technologies (ICTs) have become a vital infrastructural asset for potential use in the retention of health care providers in remote rural areas [1–5]. Though there have been substantial studies on other factors that influence retention of health workers in rural areas such as pay rise, good housing and others [6], little attention has been put to explore the influence of ICT use on retention of health workers in rural and remote areas [3, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Though there have been substantial studies on other factors that influence retention of health workers in rural areas such as pay rise, good housing and others [6], little attention has been put to explore the influence of ICT use on retention of health workers in rural and remote areas [3, 5]. Just as the case in favour of ICT use in promoting the retention of health care providers in rural areas has been made, it is also reasonable to explore the perceptions of health workers on whether ICT facilities and infrastructural development might contribute to retention in rural post-war conflict northern Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Woodward and others in 2014 which included a sample from West Bank and Gaza showed that ICT-based e-Health innovations can relieve information and communication needs of health workers in postconflict settings. [17][18][19] Another study by Hassan and others in 2017 described the implementation of a registration tool for obstetric interventions and childbirth events using e-Health in a prospective birth cohort study in six Palestinian governmental hospitals. Their study indicated that e-Health provides opportunities for quality improvement of healthcare, although its implementation in low-income and middle-income countries is still limited.…”
Section: Evidence and Rationale For E-healthmentioning
confidence: 99%